Preparation and Synthesis of Micro-Sized Carbon Material from Coconut Shell with Variation of Material Mixing Time Using a Blender for Fe Filtration of Mataram Canal Water - Hastuti, Irnawati Widya; Andriani, Nur Baeity; Pratama, Buki Wahyu; Dwandaru, Wipsar Sunu Brams (Program Studi Pendidikan Fisika UHAMKA, 2017)
This study aims to synthesis micro-sized carbon material from coconut shell leftovers or wastes using piezoelectric-based ultrasonication in liquid phase. The micro-sized carbon material produced is then utilized as a filtration material for Mataram canal water in Yogyakarta. This study begins with synthesizing the micro-sized carbon material by mixing i) mashed coconut shells, ii) 100 ml distilled water, and iii) 2 grams of detergent into a blender. The aforementioned materials are blended with mixing time variation of 30 minutes and 60 minutes. The resulted solution is left alone for a night and then ultrasonicated for 4 hours. The solution is then characterized using UV-Vis spectrophotometer. The sediments obtained from the carbon materials are characterized using X-ray diffraction (XRD) for each mixing time variation whereas scanning electron microscopy (SEM) is conducted upon the micro-sized carbon material with 60 minutes mixing time. The solution and the sediment is poured onto a filter paper, heated until dry, and fitted to a simple filtration device. Water from Mataram canal is used to test the Fe filtration ability of the micro-sized carbon material. The water samples before and after filtration are characterized using atomic absorption spectroscopy (AAS). The UV-Vis results show that increasing the mixing time of material, increases the absorbance value. Based on XRD results the synthesized micro-sized carbon material from coconut shell has an amorphous phase. The SEM result at 60 minutes of mixing time looks like an irregular bulk material with sizes of about 1 μm to 12 μm with thicknesses of around 0.6 μm to 0.8 μm. The AAS results indicate that the longer the mixing time, the lower the Fe content in the water samples after filtration.